Analisis Pengaruh Kompensasi Finansial Dan Kompensasi Non Finansial Terhadap Kinerja Karyawan Dapoer Bistik Sragen - Gumilar, Galih Cahyo, Jati Waskito,SE,.Msi (2016)
The purpose of this study was to analyze the effect of financial compensation to employee performance Dapoer Beefsteak Sragen, analyze the effect of non-financial compensation to employee performance Dapoer Beefsteak Sragen, and mengnalisis influence financial compensation and non-financial compensation to employee performance Dapoer Beefsteak Sragen. This research is quantitative descriptive. The data used is primary data collection method questionnaire data. The population in this study were all employees Dapoer Beefsteak Sragen some 58 people. Because of the number of employees is less than 100 then, the sample in this penelitaian are a number of population, ie 58 respondents. The data analysis method used: Test Instrument includes: validity and reliability test, classic assumption test include: normality test, multicollinearity, heterokedastisitas test, Tests of Hypotheses include: multiple linear regression test, F test, t test and the coefficient of determination. Research shows that the financial compensation and nonfinancial variables simultaneously significant effect on employee performance Dapoer Beefsteak Sragen with an f count> F table (24.505> 3.18). Through the analysis of the t test each variable X has t> t table ie (4.044 and 3.24> 2.003) which means the compensation of financial and non-financial compensation each have influence on employee performance Dapoer Beefsteak Sragen. Keywords: Employee Performance, financial compensation, non-Financial Compensation,